Microstructures and tensile properties of Mg-2Zn-0.8Sr-0.2Ca alloy extruded at relatively slow speed and low temperature - Yang, An (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
In this work, a new Mg-2Zn-0.8Sr-0.2Ca alloy with low content of alloying elements was subjected to extrusion at relatively low-temperatures (240 and 200°C) and slow-speed (1.0 mm/s and 0.1 mm/s). The average size and volume fraction of recrystallized grains in the extruded Mg-2Zn-0.8Sr-0.2Ca alloy gradually decreased with the reduction in extrusion rate or extrusion temperature. Some broken second phases including Ca2Mg6Zn3 and Mg17Sr2 appeared in the extruded Mg-2Zn-0.8Sr-0.2Ca alloy along with some precipitated nano-sized MgZn2 phases. The volume fraction of MgZn2 phases gradually in the alloy increased as extrusion rate or temperature decreased. High performance with yield strength of 393.1 MPa, ultimate tensile strength of 418.4 MPa and the elongation of 5.7% was obtained in the Mg-2Zn-0.8Sr-0.2Ca alloy extruded at 200°C & 0.1 mm/s. The main strengthening mechanisms could be attributed to grain-boundary strengthening, dislocation strengthening, precipitation strengthening, which were related to the change in grain size, second phases and basal texture intensity for the extruded Mg-2Zn-0.8Sr-0.2Ca alloy.
Keywords: Mg-2Zn-0.8Sr-0.2Ca alloy; extrusion; microstructure; texture; mechanical properties